Maintenance management of domestic sewage treatment plant in Klang Valley / Kamaruddin Zainuddin - Zainuddin, Kamaruddin (Faculty of Architecture, Planning and Surveying, 2013)
This dissertation is to present about maintenance management in sewage treatment plant almost in Klang valley area. Klang valleys are choosing for the further studies because normally this issue arises in the high population area. According to objective of the study, the maintenance management of sewage treatment plant is related to the community that lives nearest treatment plant location. The study was focus to the current maintenance management that is practice in sewage treatment plant and opinion of nearest residence according to the maintenance performance that was understood by residence. Sewage treatment plant (STP) or usually called waste water treatment plant is an industrial structure designed to remove biological or waste products from water. This research focused on the sewage treatment plant in residential area where the treated water will be used for other purposes. The objective is to produce an environmentally safe fluid waste stream that suitable for domestic reuse. Therefore,by using an advanced technology there is possible to reuse sewage effluent for drinking water. The objective of this research will elaborate on the current maintenance of selected sewage treatment plant and the issue on the problem arise because of the sewage treatment plant will be provided through interview the right person And the questionnaire was provide to show the opinion on the problem that caused by the sewage treatment plant nearby. Every aspect was taken into consideration the comfort level of the respondent by getting their opinions in order to improve the satisfaction of the respondents comfort towards the sewage treatment plant. Distribution of data for each question will be explained in data findings of this dissertation. This dissertation finds a modest but significant in establish conscious the respondents opinion and the finding will give the idea in improving the satisfaction level in residential area.